Inclusive neutrino and antineutrino scattering within the coherent density fluctuation model - Ivanov Martin; Antonov Anton (EPJ Web of Conferences)
The experimental data from quasielastic neutrino and antineutrino scattering on 12C are analyzed in terms of a new scaling variable ψ* suggested by the interacting relativistic Fermi gas model with scalar and vector interactions, which is known to generate a relativistic effective mass for the interacting nucleons. We construct a new scaling function fQE(ψ*) for the inclusive lepton scattering from nuclei within the coherent density fluctuation model (CDFM). The latter is a natural extension of the relativistic Fermi gas (RFG) model to finite nuclei. In this work, on the basis of the scaling function obtained within CDFM with a relativistic effective mass m*N from 0.6mN to 1.0mN, thus demonstrating its role in more details, we calculate and compare the theoretical predictions with a large set of experimental data for inclusive (anti)neutrino cross sections. The model also includes the contribution of weak two-body currents in the two-particle two-hole sector, evaluated within a fully RFG. Good agreement with experimental data is found over the whole range (anti)neutrino energies.